Tik tok: life and emotions of a teenager during covid - Douida Amina (International Journal of Social Communication, 2023)
This article aims to explore the content of videos produced by young people with the TikTok application in the context of the Covid pandemic which, since March 2020, has led to the death of millions of people around the world. They creative practices on Tiktok evolve according to a process of social mimicry. A production taking the place of a model is the source of hundreds of others wanting to different from the original. We have selected three popular productions during the pandemic for in-depth study. Our analysis is based on the approach socioanthropological which is a contemporary current of sociology understanding